KIF5A de novo mutation associated with myoclonic seizures and neonatal onset progressive leukoencephalopathy. Issue 5 (16th September 2016) - Rydzanicz, M.; Jagła, M.; Kosinska, J.; Tomasik, T.; Sobczak, A.; Pollak, A.; Herman‐Sucharska, I.; Walczak, A.; Kwinta, P.; Płoski, R.
Abstract : The KIF5A gene (OMIM 602821) encodes a neuron‐specific kinesin heavy chain involved in intracellular transport of mitochondria and other cargoes. KIF5A protein comprises the N terminal motor domain, the stalk domain and the C‐terminal cargo binding domain. The binding between KIF5A and its cargoes is mediated by kinesin adaptor proteins such as TRAK1 and TRAK2. Numerous missense KIF5A mutations in the motor and stalk domains cause spastic paraplegia type 10 (SPG10, OMIM 604187). Conversely, the role of loss‐of‐function mutations, especially those affecting the cargo binding domain, is unclear. We describe a novel de novo KIF5A p.Ser974fs/c.2921delC mutation found by whole exome sequencing in a patient with a congenital severe disease characterized by myoclonic seizures and progressive leukoencephalopathy. Since this phenotype differs considerably from the KIF5A /SPG10 disease spectrum we propose that the KIF5A p.Ser974fs and possibly other mutations which lead to truncation of the C‐terminal tail of the protein cause a novel disorder. We speculate that the unique effect of the C‐terminal truncating KIF5A mutations may result from the previously described complex role of this protein domain in binding of the TRAK2 and possibly other kinesin adaptor protein(s). Abstract :